Penggunaan Arsip Pers Masa Pendudukan Jepang Sampai dengan Revolusi Fisik di Kalimantan Sebagai Sumber Belajar Sejarah SMA - Djono Djono (Yupa: Historical Studies Journal, 2022)
A newspaper archive is a primary historical source that is relevant to be used as a source of history learning. This study aims to identify newspaper archives from the Japanese occupation to the Physical Revolution in Kalimantan which have the potential as a source of history learning. This research also intends to identify the relevance of using newspapers as a source of history learning in high school. This study uses qualitative methods using descriptive analysis techniques. Data collection was carried out through interviews and document studies. Data analysis using an interactive model includes data reduction, presentation, and concluding. The credibility test uses source triangulation techniques. This study concludes that during the physical revolution, the press was classified into a press with a colonial orientation and a press with a republican orientation. Press archives during the physical revolution were relevant to the competence of high school history learning. This relevance can be seen from the presentation of class XII learning materials with historical periods from the Japanese occupation to the period of defending Indonesian independence.